DOCUMENT European Parliament resolution on Cyprus's membership application to the European Union and the State of Negotiations (COM(2000) 702 - CS-0602/2000 - 1997/2171 (COS)). - --, -- (Études helléniques / Hellenic Studies, 2001)
DOCUMENT European Parliament resolution on Cyprus's membership application to the European Union and the State of Negotiations (COM(2000) 702 - CS-0602/2000 - 1997/2171 (COS)).